Maternal and Neonatal outcome in premature rupture of membranes - Lovereen, Salma; Khanum, Mst Afroza; Nargis, Nazlima; Begum, Shahanawaj; Afroze, Rumana (Bangladesh Journal of Medical Science, 2018)
Objective: The objective of the study was to assess the maternal and neonatal outcome in premature rupture of membranes. Material and Methods: A prospective study was carried out in the department of Obstetrics &Gynae in Ibn Sina Medical College hospital from October’15 to September’16. The sample size was 110. The maternal and neonatal outcome of pre-labour rupture of membranes in both term and preterm pregnancies was observed and statistically analyzed. Results: Incidence of PROM (premature rupture of membrane) was commonly in primigravida (62.7%). Term PROM was higher (70.92%) than PPROM (29.09%). Aetiological analysis revealed cause is unknown in most of the cases. Infection in 26.4% cases, previous history of PROM 16.3% and history of recent coitus 9.09% cases. Patient delivered by vaginal route 70.91% and LSCS 29.09%. The PROM had higher maternal morbidity (27.8%) like post partum fever 11.8%, wound infection 4.5% and chorioamnionitis 3.6%. Also higher perinatal mortality (4.5%) and morbidity (26.4%) like respiratory distress syndrome 9.09%, birth asphyxia 4.5%, septicemia 5.8%. Conclusion: Antenatal diagnosis to prevent PROM by identifying the risk factors is an important tool in management. Steroid for fetal lung maturity, antibiotics to prevent fetal and maternal infection, induction and/or augmentation of labour in due time and skilled NICU support will speed delivery, reduce hospital stay and infection as well as decrease maternal morbidity and perinatal morbidity and mortality. Bangladesh Journal of Medical Science Vol.17(3) 2018 p.479-483